Community organization and gang policy response - Curry, G. David (Journal of quantitative criminology, 1992)
Analysis of agency response networks in 21 urban areas reveals that the adoption of policy responses is significantly related to social network location. In the 1988 National Youth Gang Intervention and Suppression Program survey, agency representatives were asked to list agencies with which regular contact was maintained in the process of dealing with the youth gang problem. Policy response is measured by the adoption of four policy responses: (1) making staff training available, (2) having a policy for dealing with youth gang problems, (3) having a policy in writing, and (4) attempting to influence legislation on the youth gang problem. Rasch modeling supports the scalability of the four items. The STRUCTURE program is used to identify elements of network structure within each community-specifically cliques and equivalence structures. A generalized linear model analysis of variance of the policy response scale reveals that structural equivalence and clique membership account for 54% of the variation in policy response. An examination of clique means indicates that network structure may retard as well as enhance policy response adaptations. In policy terms, this finding suggests that network structure should be mobilized by those who wish to develop a unified, national-level response to youth gang problems at the local level.